Cavernous Carotid Artery Giant Aneurysm: Case Report and Literature Review - Packer, Lucas Willian; Vanzin, José Ricardo; Menegon, Vinicius (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
The giant aneurysm of the cavernous internal carotid artery is an uncommon event. In the case of giant aneurysmal formation, the patient presents with some signs or symptoms, reported or observed on physical examination, which reveal a possible mass effect with neurovascular compression of the aneurysm, or even a subarachnoid hemorrhage due to the rupture of the aneurysm. We report the case of a 69-year-old patient who was admitted to the emergency department, referred by the basic health unit (BHU) of her locality for neurosurgical evaluation after suffering a mild traumatic brain injury (TBI). The patient, who was asymptomatic, carried with her a tomographic computerized examination of the skull, performed one day after the incident, evidencing left nodular parasellar lesion involving the cavernous sinus, discovered at random. After more specific clinical, laboratory and imaging exams, she was diagnosed with a giant aneurysm of the cavernous segment of the left internal carotid artery (LICA) and was submitted to endovascular embolization for correction.
Keywords: aneurysm; intracranial aneurysm; therapeutic embolization